Optimizing procurement system using Nielsen’s Heuristics / Muhammad Afiq Ikmal Madzlan and Siti Nurul Hayatie Ishak - Madzlan, Muhammad Afiq Ikmal; Ishak, Siti Nurul Hayatie (Universiti Teknologi MARA, Perak, 2024)
A fitness center grapples with significant challenges related to administrative errors, prolonged purchase cycles, and supplier management issues, resulting in escalated costs and operational inefficiencies. To address these hurdles, this project aims to develop a procurement system for this fitness center, targeting the optimization of procurement activities, improvement of inventory management, and facilitation of smoother interactions with suppliers for managers, staff, and suppliers alike. The objective of this study was to identify the requirements for the procurement system, design and develop the system with integrating Nielsen's heuristics. Furthermore, a system evaluation has been conducted to test its functionality and usability to the target users. Utilizing an adapted waterfall model as the framework, the system's scope encompasses user registration, login procedures, purchase order submission, invoice generation, and equipment maintenance and management. The evaluation results demonstrated that the system meets all requirements outlined in the test plan. Additionally, feedback from both users and experts has been integrated to further refine the system. Implementation of this system will make the procurement process smoother and more organized. By prioritizing usability, efficiency, and user satisfaction, the system has the potential to optimize procurement activities, reduce errors, and ultimately improve the overall functioning of the fitness center.